2018
DOI: 10.1039/c8tc04691c
|View full text |Cite
|
Sign up to set email alerts
|

High-performance lead-free two-dimensional perovskite photo transistors assisted by ferroelectric dielectrics

Abstract: With the assistance of a ferroelectric field created by a ferroelectric polymer, the performance of perovskite photo transistors is significantly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The X‐ray diffraction (XRD) measurement was carried out on the (PEA) 2 PbI 4 thin film on a SiO 2 substrate. (Figure c) The peaks located at (0 0 L) (L = 2, 4, 6, 8, 10, 12, 14) indicated the layered structure of the 2D perovskite film, where the long organic chain was formed by organic phenylethylammonium cations (PEA + ) and the corner‐sharing octahedra halide‐metal frames were consisted by PbI 6 − anion . No residual peaks of the PEAI or the PbI 2 were observed in the XRD diagram, and the sharp peaks indicate the good crystallization of the film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The X‐ray diffraction (XRD) measurement was carried out on the (PEA) 2 PbI 4 thin film on a SiO 2 substrate. (Figure c) The peaks located at (0 0 L) (L = 2, 4, 6, 8, 10, 12, 14) indicated the layered structure of the 2D perovskite film, where the long organic chain was formed by organic phenylethylammonium cations (PEA + ) and the corner‐sharing octahedra halide‐metal frames were consisted by PbI 6 − anion . No residual peaks of the PEAI or the PbI 2 were observed in the XRD diagram, and the sharp peaks indicate the good crystallization of the film.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular configurations of MoS 2 and (PEA) 2 PbI 4 are presented in Figure S1a,b of the Supporting Information. It was previously reported that 2D materials were layered structure and the force between layers was van der Waals force . Raman spectrum was measured on the MoS 2 flakes to determine the thickness via energy difference between E 2g 1 and A 1g ( Figure a) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the photoresponse tests were carried out under the illumination of a 470 nm monochromatic light source. Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: D and 2d Perovskite Phototransistorsmentioning
confidence: 99%
“…Wang et al investigated ferroelectric‐effect on performance of BGBC phototransistor (Figure d) with same 2D layered (PEA) 2 SnI 4 as channel layer in 2018 . Ferroelectric polymer poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE)) served as a dielectric insulator layer in the devices, forming three different polarization states including pristine, polarization “up,” and polarization “down,” respectively, as shown in Figure e–g.…”
Section: D and 2d Perovskite Phototransistorsmentioning
confidence: 99%